Prenatal Development of Tibia and Fibula in Goat (Capra hircus) - Chaudhary, Avnish (Indian Journal of Veterinary Anatomy, 2020)
Present study was conducted on the tibia and fibula of goat, irrespective of sex and breed from 35-148days of gestation. The fetuses were divided into three groups viz; Group I (< 50 days of gestation), Group II (>50 days and < 100 days of gestation), and Group III (> 100 days of gestation till parturition) comprising of 8fetuses in each group. The hind limb of each fetus was stained with either Alizarin red-S stain or Alizarin red-SAlcian blue combined stain to study the centres of ossification. At 44 days of gestation, the cartilaginousminiatures of tibia were present. At 46 days of gestation, two centres of ossification were seen, one for thediaphysis of tibia and another for the fibula. The center of ossification for the tibial tuberosity was exhibited at62 days of gestation. The centres of ossification for the proximal and distal extremities of tibia appeared asAlizarin red stained spots in the centre of the cartilaginous masses at 135 days of gestation.